What does it mean to belong? An in-depth look at the effects a sense of belonging in emerging adulthood has on coping - Torgerson, Chelsey Nicole (Kansas State University, 2018)
Belonging to groups has been found to lead to many positive outcomes, including acting as a buffer for maladaptive coping behaviors, in the lives of emerging adults. Less is known about how belonging may act as a protective factor to engaging in unhealthy behaviors, less is known in regards to how group coping norms of the groups emerging adults belong to impact the motivations for coping and subsequently coping mechanisms. Further, belonging is a necessary component to life; however, less is known about how emerging adults understand what it means to belong. This dissertation includes two studies focused on belonging in emerging adulthood. Both studies utilized participants recruited from Amazon Mechanical Turk (Mturk). In study 1, a quantitative study (N = 438) was conducted to further explore how group coping norms moderates the associations between group belonging and individual motives for coping. Additionally, coping behaviors were included to understand how belonging to groups is associated with coping motives and coping behaviors. Results from study 1 indicated that while belonging was not significantly predictive of motivations and functions of using specific behaviors, unhealthy group coping norms were positively predictive of motivations for and functions of behaviors for coping purposes. Moreover, the interaction term (belonging X unhealthy group norms) yielded one significant path indicating that belonging to groups may be protective of using sex to cope even when unhealthy group norms are present. Additionally, belonging was negatively associated with drug frequency and positively associated with healthy supportive and self-soothing coping. Further, several coping motives were positive predictors of both unhealthy and healthy coping behaviors. In study 2, a qualitative study (N = 422) using open-ended questions was conducted to hear from emerging adults about their experiences of belonging. A thematic analysis approach was used to code participant responses before categorization and identifying themes. Participant responses indicate that emerging adults belong to groups based on personal identity, religious and spiritual affiliations, life stage and circumstances, educational group associations, professional association, significant relationships, social change initiatives, shared interests and activities, online connections. Moreover, themes outlining what it means to belong to emerging adults include embraced, increased self-confidence, greater life meaning, experience of a safety net, commonalities among group members, relationship component to group belonging, and fitting in and conformity. Before belonging to groups, results indicate that becoming a member of the group is necessary. Reasons for joining groups, group membership through intentionality, formal group entrance process, group membership as a natural process, group membership through identity formation, and group membership in an online context are all components of joining groups for emerging adults. Participants described the process of belonging with the following themes: building investment and intimacy, messages of inclusion, developing connection and community, mutual support, positive feelings that foster belonging, and individual growth and development and the process of belonging. Finally, participants identified what they get from belonging to groups which included a sense of belonging, feeling included and a part of something, personal growth needs, emotional needs, communal needs, work needs, and giving back and volunteering needs. The findings of this qualitative study indicate a need to further understand the belonging phenomenon in emerging adults across many populations. Research, clinical, and practical implications are outlined and provided.
Keywords: Belonging; Coping; Emerging adults; Group association